PENINGKATAN PRESTASI BELAJAR SISWA MELALUI PENDEKATAN LIFE SKILL DALAM PEMBELAJARAN KERTAKES DI SD - Yuyarti Yuyarti (JURNAL LITBANG PROVINSI JAWA TENGAH, 2010)
Various attempt have been made to improve the quality of learning, among others through various refinements of the curriculum, syllabus development, textbook procurement, use of strategies and approaches learning models, improve the quality of learning throughh various training and qualification improvement of education personel. Educational innovation in now led to the formation of life skills, an integrated learning model (integrated learning) and this contextual learning is one model that leads to learning life skills. Against this background through life skills approach to learning that have not been implemented Kertakes primary school. The quality of learning in primary school are still low. Kertakes learning tends to be theoretical, and associate with the environment and still applicable. The research objective: (1)Make a model of learning with the skills approach to Kertakes subjects; (2) Improving students learning achivement; (3) Increase student activities and analyze the skills of teachers in teaching and learning activities. This research is a classroom action research using the planning cycle, action, observation and reflection. Techniques of data collection in this study using a test sheet to reveal students learning achievement, and observation sheets to analyze the activity of teachers in managing learning and teaching. The results obtained through life skills in Kertakes. Kertakes subjects can increase student learning achievement, learing to manage skilled, besides that students have a desire to develop what they practice for future supplies if they did not resume again next to school. The work is simple provision of life skills, social skills, and academic skills. Based on these results, suggested primary school teachers in the learning Kertakes wuth dyed batik material, intended to find the concepts they learn about so that the learning environment more meaningful.